The Berlin Site of Luisenstadt and the Figure of St Michael: A Case Study on Iconic Space - Engelbart, Rolf (Material religion, 2016)
The article focuses on the figure of St. Michael on top of the front façade of St. Michael's Church, which is situated in the Mitte district of Berlin, Germany, formerly called Luisenstadt. Following a relational approach, according to which single elements only get an explicit and distinct meaning in connection to other elements, the contribution first. describes the site in which the figure of St. Michael is embedded and reconstructs its spatial iconicity. Second, it analyzes the statue as a polysemic and thus contested icon and shows how political, artistic, touristic, and religious meanings interact with each other in and through the figure.